Prototype Model for Defect Inspection of Vials - C.R. , Vishwanatha; V. , Asha (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents a prototype model for defect inspection of medicine vials. The proposed model for inspection of medicine vials ensures that the quality of vials meets the required standards. Because product quality is the essence of enterprises, especially pharmaceutical products, which are closely concerned with people’s health, product quality testing is a significant part of the production process. It is inevitable that various defects emerge during the pharmaceutical manufacturing process in the medicine vials, which may greatly affect the product quality and reduce the productive efficiency. Even a minor defect on the surface of the vial may cause a chemical reaction and contaminate the chemical composition of the filled medicine. When the defect is significant, the chemical reaction may drastically happen due to environmental exposure of the fluid and may remain unchecked in many cases. This in turn becomes life-threatening to the already suffering patient to whom the medicine is to be injected. Pharmaceutical drug vials need to be inspected in order to ensure that the vial meets predetermined specifications and does not harm the patient.